Consumer-based coping within the United States during COVID-19: impacts of working from home - Melissa Carsten; Cara Peters; Stephanie Lawson (Cogent Business & Management, 2024)
The COVID-19 pandemic forced many people to shift how to they engage in work and consumption behaviors. This study examines the remote working conditions that influence employee stress and whether work related stress influenced consumer-based coping behaviors in the height of the pandemic. Data were collected from 232 working adults to examine whether role conflict and boredom relate to avoidant (alcohol consumption) and confrontative (exercise frequency) consumer coping behaviors via perceived stress. Results show direct relationships between work conditions, stress, and consumer based coping; however the mediation hypotheses were not supported. Implications for work stress and consumer coping are discussed.
Keywords: 650; Consumer coping behavior; role conflict; boredom; stress; drinking behavior; exercise behavior